2009
DOI: 10.2514/1.42203
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Deployment Control of Spinning Space Webs and Membranes

Abstract: Akademisk avhandling som med tillstånd av Kungliga Tekniska Högskolan i Stockholm framlägges till offentlig granskning för avläggande av teknologie doktorsexamen måndagen den 8:e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 102 publications
(121 reference statements)
0
11
0
Order By: Relevance
“…Several control strategies of membranes deployment were studied in order to avoid re-coiling in one-step deployment [9,11,12]. A 20 m diameter membrane reflector was deployed at the end of a spacecraft using a one-step method during the Znamya-2 experiment in 1993 [9], which demonstrated that a spin deployment of a gossamer structure can be controlled by simple means.…”
Section: Control Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several control strategies of membranes deployment were studied in order to avoid re-coiling in one-step deployment [9,11,12]. A 20 m diameter membrane reflector was deployed at the end of a spacecraft using a one-step method during the Znamya-2 experiment in 1993 [9], which demonstrated that a spin deployment of a gossamer structure can be controlled by simple means.…”
Section: Control Methodsmentioning
confidence: 99%
“…Four cameras on the central hub were used to record the web deployment and stabilization phases. The space web was folded around the central hub in a star folding pattern [12] and deployed by centrifugal forces acting on the attached daughters.…”
Section: Experiments Designmentioning
confidence: 99%
See 3 more Smart Citations